Strontium-loaded multifunctional gelatin methacryloyl hydrogels for type-H vascularized bone regeneration under osteoporotic conditions - Yuwei He; Fanchun Zeng; Hongyu Quan; Lanyi Liu; Jingjin Dai; Hong Jiang; Shiwu Dong (Materials Today Bio)
Osteoporosis (OP) is a clinically prevalent bone disease, under which excessive activation of osteoclasts (OCs) significantly delays bone regeneration. In this context, bone regeneration necessitates not merely the facilitation of osteogenesis and the suppression of resorption, but also more stringent requirements pertaining to vascularization, particularly type-H blood vessels. Recently, strontium (Sr) has emerged as a ''dual-action bone agent'', enhancing bone formation while suppressing bone resorption, yet still receives inadequate attention. Given that PDGF-BB secreted by osteoclast progenitors (pOCs) could induce type-H-related vascularization during coupling with osteogenesis, the regulatory effect of Sr2+ on osteoclastogenesis need to be further studied and utilized in vascularized bone regeneration. Here, we synthesized Sr-substituted layered double hydroxide (Sr-LDH) by partially substituting divalent metal ions in LDH with Sr2+, and encapsulated the surface-modified Sr-LDH into QK peptide-incorporated gelatin methacryloyl (GelMA) to form a composite hydrogel GelMA-QK/Sr-LDH@PDA (GLQ). This multifunctional hydrogel integrated the osteogenic and antiresorptive properties of Sr-LDH, exhibited significant bone regeneration efficacy under osteoporotic conditions. Furthermore, our study found that GLQ could stimulate bone marrow derived macrophages (BMMs) proliferation and preserve pOCs while suppress OC maturation, which further facilitated the expression of PDGF-BB and promoted type-H vessels development in the bone defect area. Taken together, the multifunctional composite hydrogel holds significant clinical implications for future treatment of osteoporotic bone defects.